Theoretical research of the system of automatic control dive of the screw piles - I. V. Lazuta; E. F. Lazuta (Вестник СибАДИ, 2017)
Considerable attention in the research of the system of automatic control dive of the screw piles is paid the constructive parameters of the system. The authors propose static characteristics of the output parameters of the system and set the limits of variation of constructive parameters. Also, held an analysis of the quality of regulation of the system, substantiates the researched parameters and set depending the quality of regulation and the effectiveness of dive piles from the investigated parameters.